PEMANFAATAN BUKU KIA UNTUK PERSIAPAN PERSALINAN DAN PERENCANAAN KONTRASEPSI PASCA SALIN PADA IBU HAMIL - Khusniyati, Etik; Purwati, Heni; Meilinawati SB, Elies; Ibnu, Faisal (Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Background: One of the government's efforts to reduce MMR, IMR and reduce complications during pregnancy include the activities of the Mother Love Movement, Strategy Making Pregnancy Safer and the Duplication of Mother and Child Health Books. The KIA handbook as an educational tool and an effort to increase information on pregnant women. Objective: This study aims to explore related to the use of the KIA handbook as a source of information, Birth Plan and Postpartum Contraception Planning. Methods: This study uses a concurrent triangulation strategy by collecting quantitative and qualitative data together. The sample in this study was 30 pregnant women with total sampling technique. Data analysis with a comparison of quantitative data and qualitative data. Results: The results of the study showed that out of the 15 respondents who had good use of the KIA handbook, the majority had good labor preparation. While of the 9 respondents who used the KIA handbook with sufficient categories, the majority also had good childbirth preparations. Of the 15 respondents who had good use of the KIA handbook, the majority had made contraceptive preparations. While of the 6 respondents who had less use of the KIA handbook, none planned for postpartum contraception. Conclusion: The conclusion is that the better the use of the KIA handbook, the better the preparation of labor and post-partum contraceptive planning.